Putting purpose into practice: The economics of mutuality - Colin P. Mayer; Bruno Roche (Oxford University Press, 2021)
The book provides a detailed and practical description of how companies can put purpose into practice in their organizations. Based on a ground-breaking research project on the Economics of Mutuality undertaken jointly by the Säid Business School at the University of Oxford and Mars Catalyst, the think tank of Mars Inc., the food and beverages company, over a period of five years, the book describes how purpose promotes business growth and performance. In particular, it gives a highly accessible and readable account of how companies can determine and implement their corporate purposes, and how, by so doing, they address critical issues in their ecosystems, such as rising inequality and environmental degradation, while delivering superior performance and resilience. The book will equip executives, managers, investors, policymakers, academics, and students with tools to understand the way in which companies can build purpose-centric businesses, map and orchestrate stakeholder ecosystems, identify untapped resources, create unconventional partnerships, measure and manage performance beyond financial reporting, and adopt a new definition of profit to promote corporate purposes. The book includes fourteen case studies of companies of varying sizes, sectors, and geographies that sought to put purpose into practice. They provide deep insights into the way in which companies have delivered corporate purpose and the challenges they faced in doing this. The book stresses both the opportunity and obligation on business to reposition itself to address the changing needs of society and the planet in the twenty-first century.
Keywords: 330; purpose; practice; mutuality; performance; ecosystems; partnerships; measurement; Betriebswirtschaftliches Ziel; Corporate Social Responsibility; Sozialwirtschaft; Genossenschaft; Sozialkapital; Stakeholder; Welt